Epidemiology of neurodegenerative diseases in the East African region: A meta-analysis - Onohuean, Hope; Akiyode, Abraham Olutumininu; Akiyode, Oluwole; Igbinoba, Sharon Iyobor; Alagbonsi, Abdullateef Isiaka (Frontiers in Neurology, 2022)
Introduction There is a scarcity of epidemiological data on neurodegenerative diseases (NDs) in East Africa. This meta-analysis provides the regional prevalence of NDs, their contributing factors, and evidence of change over time concerning gender per age or year. Methods Articles were retrieved from electronic databases following the PRISMA standard. Results Forty-two studies were reviewed, and 25 were meta-analyzed with a random-effects model. The pool estimate proportion of 15.27%, 95% CI (0.09–0.23) (I2 = 98.25%), (Q = 1,369.15, p < 0.0001) among a population of 15,813 male/female and 1,257 with NDs. Epidemiological characteristics associated with NDs include Dyskinesias prevalence 55.4%, 95% CI (13.5; 90.9), I2 (96%) and subsistence farming prevalence 11.3%, 95% CI (5.8; 20.9), I2 (99%). Publication bias by Egger test was (z = 4.1913, p < 0.0001), while rank correlation test using Kendall's model was (tau = 0.1237, p = 0.3873). Heterogeneity (R2 design = 5.23%, p design < 0.0001; R2 size = 52.163%, p size < 0.001; and R2 period = 48.13, p period < 0.0001. Covariates (R2 design + size + period = 48.41%, p < 0.001). Conclusion There is a high prevalence of NDs in the East African region, which could impact life expectancy, morbidity, and quality of life. Thus, early screening and regular surveillance could assist in management strategies.